Computer Application for the Evaluation of the Dento-Somato-Facial Aesthetic Balance - Oana Ţănculescu; Cristina Ifteni; Gabriela Ifteni; Cristina Iordache; Corina Cristescu; Adrian Doloca (Romanian Society of Oral Rehabilitation, 2012)
DSF (Dento-Stomato-Facial) Aesthetic Software is an application that focuses on aesthetic evaluation based on the following inter-related directions: body aesthetics, dental-facial aesthetics, dento-gingival aesthetics, dental-dental aesthetic and dental aesthetics. The application employs different images processing technics and the modern .net development platform. The application contributes to a better identification and use of the dento-facial and somatic aesthetic evaluation criteria. The software can display all the determined measurements or only those which diverge from the normal ones. The final reports can be presented either superimposed on the patient picture showing the deviated segments or on a standard image from the software library which can be also access at any time though the help function. Although the application can reveal the deviated values from the normal ones, thus pointing towards a diagnostic, the final interpretation however belongs to the dentist. The practitioner will establish the final diagnostic by correlating the data obtained from the computer application with that from clinical and paraclinical evaluation which is necessary for a complete and complex approach of the case.